2021
DOI: 10.1093/hmg/ddab058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LRRK2 missense variants in the accelerating medicines partnership Parkinson’s disease cohort

Abstract: Pathogenic missense variants in the leucine-rich repeat kinase 2 (LRRK2) gene have been identified through linkage analysis in familial Parkinson disease (PD). Subsequently, other missense variants with lower effect sizes on PD risk have emerged, as well as non-coding polymorphisms (e.g. rs76904798) enriched in PD cases in genome-wide association studies. Here we leverage recent whole-genome sequences from the Accelerating Medicines Partnership-Parkinson’s Disease (AMP-PD) and the Genome Aggregation (gnomAD) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…In a recent analysis of whole‐genome sequencing data from the Accelerating Medicines Partnership‐Parkinson's Disease cohort, Bryant and colleagues found that the 5′ variant rs76904798 was associated with LRRK2 p.R1514Q and p.N2081D 33 . We confirmed the co‐inheritance of these variants with rs76904798 in a data set that is ~20 times larger and also found a significant difference in the allele distribution of p.S1647T after removing rs76904798 carriers.…”
Section: Discussionsupporting
confidence: 74%
“…In a recent analysis of whole‐genome sequencing data from the Accelerating Medicines Partnership‐Parkinson's Disease cohort, Bryant and colleagues found that the 5′ variant rs76904798 was associated with LRRK2 p.R1514Q and p.N2081D 33 . We confirmed the co‐inheritance of these variants with rs76904798 in a data set that is ~20 times larger and also found a significant difference in the allele distribution of p.S1647T after removing rs76904798 carriers.…”
Section: Discussionsupporting
confidence: 74%
“…All the definite LRRK2 mutations are in the catalytic domains and may result in hyperactivation of the kinase domain [ 3 , 53 ]. LRRK2 is involved in a large array of cell biological processes, and the disease mechanism may reflect important roles in microtubule function and Rab proteins as phosphorylation substrates [ 2 , 54 ].…”
Section: Autosomal Dominant Formsmentioning
confidence: 99%
“…In a recent analysis of whole-genome sequencing data from the Accelerating Medicines Partnership-Parkinson's Disease (AMP-PD) cohort, Bryant et al found that the 5' variant rs76904798 was associated with LRRK2 p.R1514Q and p.N2081D 33 . We confirmed the coinheritance of these variants with rs76904798 in a dataset that is ~20 times larger and also found a significant difference in the allele distribution of p.S1647T after removing rs76904798 carriers.…”
Section: Discussionmentioning
confidence: 99%